Manajemen Berbasis Sekolah Untuk Meningktakan Kualitas Sekolah Yang Bercirikan Buddhis - haudi haudi (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
The management of early childhood education units, basic education, and secondaryeducation is carried out based on minimum service standards with school/madrasah-basedmanagement principles. The school management in question is a form of autonomy in themanagement of education in primary and secondary education units which showsindependence, partnership, cooperation, participation, openness, and responsibility.Research on the implementation of SBM in the world of education has often been carriedout with the evidence that many journals have been published. Some researchers focus onthe leadership of principals, teachers and the quality of student education. There are noresearchers who have paid attention to the implementation of SBM in schools withBuddhist characteristics, especially the implementation of Pancasila, the SigalovadaSutta, and the Dasa Raja Dhamma. Therefore, the focus of this research is on theapplication of Buddhist values that are applied by teachers and students, in teaching andlearning activities as well as in daily life. This study aims to determine whether DSschools have implemented SBM with Buddhist values. The research was conducted usingdescriptive qualitative analysis with primary data sourced from resource persons and keypersons using interview, observation, and documentation methods. The sample taken inthis study amounted to 9 informants. The results of the study show that SBM withBuddhist values is only implemented by students and some teachers, while teachers,school officials and administration still have not implemented SBM with Buddhist values